EPIDEMIOLOGY OF ROTAVIRUS INFECTION IN CHILDREN UNDER FIVE YEARS IN DR. SOETOMO HOSPITAL, SURABAYA (2015-2019): Gambaran Epidemiologi Kasus Infeksi Rotavirus Pada Balita di RSUD Dr. Soetomo Pada Tahun 2015-2019 - Ana Bilah, Aisah Nur; Dinana, Zayyin; Maharani, Aussie Tahta; Fitria, Anisa Lailatul; Juniastuti; Athiyyah, Alpha Fardah; Darma, Andy; Gunadi Ranuh, I Gusti Made Reza; Sudarmo, Subijanto Marto; Yamani, Laura Navika (Universitas Airlangga, 2024)
Background: Diarrhea is the first cause of death for children under five years of age worldwide. In Indonesia, diarrhea cases due to rotavirus infection tend to be detected throughout the year. Purpose: The study was to determine the epidemiology of diarrhea cases due to rotavirus infection of pediatric patients in Dr. Soetomo Hospital, Surabaya based on the variables of person, place, and time. Methods: This type of research uses both descriptive and quantitative methods. The samples used were cases of rotavirus infection in toddlers in Dr. Soetomo Hospital, Surabaya in 2015–2019. Results: From 2015 to 2019, there were about 110 cases (31.98%) of acute diarrhea caused by rotavirus infection at Dr. Soetomo Hospital, Surabaya. The findings revealed that the majority of rotavirus infections (42.73%) occurred in children aged 6-11 months followed 12-23 months (35.45%) and were male (56.36%). The highest cumulative incidence was observed in August 2018 and February 2029, with a value of 1,0. Rotavirus infection was most common among children living in Gubeng sub-District, with 19 cases (17.27%). Conclusion: Epidemiological studies of rotavirus infection by person, place, and time reveal the distribution of disease cases and enable targeted interventions to respond to the disease.